Epidemiology of major infectious diseases in indigenous and ethnic minority peoples of the Asia Pacific region - Gilmour, Elizabeth Susan (Curtin University, 2022)
This study found a high prevalence of HIV, tuberculosis (TB), malaria, and soil-transmitted helminth (STH) infection within indigenous and ethnic minority populations of the Asia Pacific region. These populations had a higher risk of HIV, malaria, and STH infection than comparative reference majority populations and were also disadvantaged across TB diagnosis and treatment metrics. Vulnerable populations must be considered if the Sustainable Development Agenda goal of ending these pandemics by 2030 is to be achieved.